Quantificando Polarização, Coesão e Permeabilidade na Câmara dos Deputados do Brasil - Baker, Frederico; Benevenuto, Fabricio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
We present a network analysis of voting behavior in the Brazilian Chamber of Deputies from 2003 to 2023, focusing on three structural dimensions of legislative dynamics: polarization, party cohesion, and ideological permeability. To measure polarization, we apply structural balance theory to signed networks, examining how the relative frequency of specific triadic configurations, particularly those with two negative and one positive edge, signals the consolidation of antagonistic political blocs. For party cohesion, we quantify how consistently members of each party cluster within ideological communities detected through modularity optimization. To evaluate ideological permeability, we simulate influence diffusion using a network-based adaptation of the classical SIR model, capturing how political positions can propagate through the legislative graph depending on node centrality and edge polarity. Our results reveal a marked rise in polarization beginning in the 55th legislature, reflected by a structural shift toward triads driven by shared opposition rather than shared agreement. While the Workers’ Party (PT) maintained high internal cohesion, its reach across the network declined sharply in the 56th legislature. Although focused on institutional dynamics, our findings also reflect broader patterns observed in digital political discourse, where processes of ideological clustering and antagonistic alignment are likewise prevalent. In this sense, the structural features identified in legislative networks may help inform the analysis of polarization and influence in both formal political contexts and digitally mediated environments.